Pengaruh Pemberian Modifikasi Non-Nutritive Sucking (NNS) Terhadap Nilai Premature Infant Pain Profil–Revised (PIPP-R) Pada Neonatus yang Diberikan Vaksin Hepatitis B - Indrasari, Neneng; Zulfia, Rahmatuz; Alfianur, Alfianur; Sulidah, Sulidah; Hasriana, Hasriana (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT There are various kinds of non-pharmacological pain management that can be applied to neonates, including Non-Nutritive Sucking (NNS). NNS is a method of stimulating the neonate’s sucking reflex, providing relief from acute pain. Premature Infant Pain Profile-Revised (PIPP-R) is a neonatal pain assessment that has validity, reliability, and feasibility. This research aimed to describe the process of determining non-pharmacological pain management that was applied with non-pharmacological techniques or management using NNS or finger sucking to reduce pain. The method used was a quasi-experimental design to assess the effect of NNS modification on the value of PIPP-R. The sample was taken from the respondents who were giving the Hepatitis B vaccine. The results showed that there was an effect of giving the NNS modification on the value of PIPP-R in neonates who were given the Hepatitis B vaccine at H. Jusuf S.K Tarakan Hospital, North Kalimantan Province, as evidenced by a p-value <0.05. The mean values after administrating the Hepatitis B vaccine intervention showed that there was a difference in the mean value in the intervention group which was more effective in reducing the scale based on the PIPP-R scale with NNS modification compared to the control group. Granting the NNS modification on the value of PIPP-R in neonates was more effective in the intervention group than that in the control group. Keywords: Hepatitis B, Neonates, NNS, Pain, PIPP-R  ABSTRAK Ada berbagai macam manajemen nyeri non farmakologis yang dapat diterapkan pada neonatus, diantaranya adalah Non-Nutritive Sucking (NNS). NNS adalah metode untuk merangsang refleks mengisap neonatus, memberikan bantuan dari nyeri akut. Prematur Infant Pain Profile Revised (PIPP-R) merupakan pengkajian nyeri neonatus yang memiliki validitas, reliabilitas, dan kelayakan. Penelitian ini bertujuan menggambarkan proses penentuan manajemen nyeri non farmakologis yang dapat diterapkan dengan teknik atau manajemen non farmakologis menggunakan NNS atau hisap jari untuk mengurangi nyeri. Desain yang digunakan yaitu desain Quasi eksperimental untuk menilai pengaruh pemberian modifikasi NNS terhadap nilai PIPP-R. Pengambilan sampel pada responden yang diberikan vaksin Hepatits B. Data yang diperoleh yaitu ada pengaruh pemberian modifikasi NNS terhadap nilai PIPP-R pada neonatus yang diberikan vaksin Hepatitis B di Rumah Sakit H. Jusuf S.K Tarakan Provinsi Kalimantan Utara dibuktikan dengan nilai p <0.05. Nilai rata-rata setelah pemberian tindakan vaksin Hepatitis B menunjukkan terdapat perbedaan nilai rata-rata pada kelompok intervensi lebih efektif dalam menurunkan skala nyeri berdasarkan skala PIPP-R dengan modifikasi NNS dibandingkan kelompok kontrol. Pemberian modifikasi NNS terhadap nilai PIPP-R pada neonatus lebih efektif pada kelompok intervensi dibandingkan kelompok kontrol. Kata Kunci: Hepatitis B, Neonatus, NNS, Nyeri, PIPP-R